Short communication. Real-time ultrasonography for early pregnancy diagnosis and incidence of embryonic/foetal mortality in farmed Iberian red deer hinds - Gomez-Nieto, J. A.; Santiago-Moreno, J.; Landete-Castillejos, T.; Gallego-Martinez, L.; Garcia-Diaz, A. J. (Spanish Journal of Agricultural Research, 2011)
<span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;" lang="EN-US">The main objective of the present study was to evaluate the accuracy of the trans-rectal ultrasonography technique applied to the Iberian red deer hinds since it has not been previously documented in Spain. Experimentation was also used to test the hypothesis that a lower fertility in young hinds could be due to an increment in embryonic or foetal mortality. For this purpose, 116 hinds divided in three groups depending on its age (young, adults and senescent) were examined by rectal ultrasonography and the different foetal structures measured two months after the males were removed from the groups of hinds. With these data, specificity and predictive value of negative diagnoses of the technique has been calculated. Trans-rectal ultrasonography is an accurate technique to use in Iberian red deer dams with overall levels of pregnant detection near to 92%. Finally, the youngest hinds showed poorer fertility rates (17.24% <span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPS-ItalicMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;" lang="EN-US">vs. <span style="font-size: 10pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;" lang="EN-US">59.30% and 58.33% of senescent and prime-age respectively) and also higher of embryonic or foetal mortality (2 deaths out of 7 positive pregnant diagnoses compared with no deaths in the senescent group and 4 deaths out of 39 positive pregnant diagnoses in the prime-age group).